2020
DOI: 10.3389/fimmu.2020.00419
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases Are Potential Biomarkers of Pulmonary and Extra-Pulmonary Tuberculosis

Abstract: Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinase (TIMPs) are potential regulators of tuberculosis (TB) pathology. Whether they are candidates for non-sputum-based biomarkers for pulmonary TB (PTB) and extra-pulmonary TB (EPTB) is not fully understood. Hence, to examine the association of MMPs and TIMPs with PTB and EPTB, we have measured the circulating levels of MMPs 2,3,7,8,9,12, and 13) and TIMPs (TIMP-1, 2, 3, and 4) in PTB, EPTB and compared them with latent tuberculosis (LTB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…In a variety of settings, MMPs and TIMPs are known biomarkers of pulmonary and extrapulmonary TB. 10 , 11 , 20 Several MMPs are upregulated in blood, sputum, and bronchoalveolar lavage of individuals with active TB. 15 , 35 , 36 , 37 , 38 , 39 In addition, MMP levels correlate with lung pathology, with plasma concentrations of several MMPs being associated with radiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of settings, MMPs and TIMPs are known biomarkers of pulmonary and extrapulmonary TB. 10 , 11 , 20 Several MMPs are upregulated in blood, sputum, and bronchoalveolar lavage of individuals with active TB. 15 , 35 , 36 , 37 , 38 , 39 In addition, MMP levels correlate with lung pathology, with plasma concentrations of several MMPs being associated with radiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Both MMPs and TIMPs are also biomarkers of extrapulmonary TB. 20 We hypothesized that baseline plasma levels of MMPs and TIMPs would be associated with adverse treatment outcomes among patients with PTB. To test this hypothesis, we examined the baseline levels of MMPs and TIMPs in 2 different nested case-control studies of favorable vs adverse treatment outcomes in a cohort of individuals with PTB in Chennai, India.…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker analysis conducted in patients with HIV/OI revealed that levels of Tr-Gal-9 markedly reflect the disease severity of the co-infected individuals [ 53 , 96 ]. The Tr-Gal-9 may be generated via cleavage by MMP-9, which has also been proposed to be a non-sputum-based biomarker for differentiating pulmonary TB and extrapulmonary TB [ 97 ].…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…Among the studied proteins, MMP-2 had the highest discriminative potential shown on the basis of the area under the ROC curve (AUC) in both 3-group and 2-group comparisons as well as the cross-validation based elastic-net feature selection. There are several reports on the role of MMP-2 in TB, but none indicate a diagnostic potential of the enzyme in pediatric TB [ 37 , 41 , 42 , 43 , 44 ]. In a cellular model of TB meningitis, Green et al demonstrated that conditioned medium from M.tb -infected primary human monocytes down-regulated the microglial constitutive MMP-2 gene expression and secretion [ 37 ].…”
Section: Discussionmentioning
confidence: 99%